Comparison of the orientation of small-scale electron density irregularities and F region plasma flow direction. - Tereshchenko, E.D.; Rietveld, Michael T.; Brekke, Asgeir; Khudukon, B.Z.; Kozlova, M.O.; Evstafiev, O.V.; Nygren, T. (European Geophysical Society, 2000)
Results are shown from an experimental campaign where satellite scintillation was observed at three sites at high latitudes and, simultaneously, the F region plasma flow was measured by the nearby EISCAT incoherent scatter radar. The anisotropy parameters of field-aligned irregularities are determined from amplitude scintillation using a method based on the variance of the relative logarithmic amplitude. The orientation of the anisotropy in a plane perpendicular to the geomagnetic field is compared with the direction of F region plasma flow. The results indicate that in most cases a good agreement between the two directions is obtained.